弧齿锥齿轮研齿运动轨迹模型的研究 - 肖春芳 (Jixie chuandong)
The three positions and multi-position point reciprocating lapping movement trajectory model is analyzed. The S0, H1, T1 three points V, H value calculation method and adjustment method are determined. The experiment proves that the lapping mode of cycle to the lapping, the adjustment is simple, parameter setting is convenient, and can be very good control of lapping process, the whole tooth surface lapping or specify local lapping effect is got.